Managing Student Stress in English Language Learning: A Case Study at Sunan Doe Institute - Bayu Islam Assasaki (Journal of Educational Management Research, 2026)
This study investigates the significant sources of stress experienced by students learning English in a non-English-speaking academic environment. Previous research indicates that English learners in EFL settings often encounter psychological, linguistic, and sociocultural barriers that impede the development of proficiency, particularly when institutions mandate English as the medium of instruction. In line with this context, the Sunan Doe Institute has implemented intensive English policies, yet many learners continue to report anxiety and performance pressure. This mixed-method study involved 150 students at three proficiency levels and 10 English lecturers, employing surveys, interviews, focus group discussions, and classroom observations to obtain comprehensive data. Quantitatively, the results reveal that fear of negative evaluation, low self-efficacy, and peer comparison are the most significant psychological stressors. Linguistic challenges, particularly pronunciation accuracy, grammatical mastery, and limited vocabulary, emerged as additional pressure points. Environmental and cultural factors, including limited English exposure, unfamiliar cultural references, and insufficient interactive practices, further elevate students’ anxiety. Qualitative findings reinforce these patterns, showing that low confidence and constrained opportunities for authentic communication hinder progress across proficiency levels. The study contributes to a deeper understanding of stress dynamics in EFL contexts and recommends culturally responsive, supportive, and interaction-rich pedagogical strategies to strengthen learner motivation and well-being.